Plasma Activated Water Assisted Ultrasonic Extraction of Polysaccharides from Yellow Cauliflower and Its Hypoglycemic Activity - Han ZHANG; Cheng YANG; Guiyun CHEN; Shuhong LI; Ye CHEN (Shipin gongye ke-ji)
To optimize the polysaccharides extraction process from Hemerocallis citrina Baroni and investigate the hypoglycemic activity of polysaccharides in vitro, the plasma activated water (PAW) was employed in conjunction with ultrasound treatment to improve the polysaccharides extraction rate. The optimum extraction rate was determined by using a single-factor experiment and response surface design. Then, the polysaccharides were purified using Sephadex G-100 dextran gel chromatographic column to obtain the pure polysaccharides from Hemerocallis citrina Baroni (HCP). The structure of HCP was identified and its hypoglycemic activity was evaluated by the approval α-glucosidase and α-amylase inhibition experiments. The results indicated that the optimal process parameters were liquid-solid ratio of 23 mL/g, extraction time of ultrasound 60 min, PAW preparation time of 90 s, in which the maximum extraction rate of Hemerocallis citrina Baroni polysaccharides was 36.33%±0.04%. The total sugar content, protein content, and uronic acid content of HCP were 88.07%±2.25%, 2.72%±0.04%, and 7.27%±0.44%, respectively. HCP was an acidic heteropolysaccharide with α-pyranose configuration, consisting of fucose, rhamnose, arabinose, galactose, glucose, mannose, and galacturonic acid. The molecular weight of HCP was 8.056 kDa. The SEM showed that HCP was sheet-like with a rough surface. Additionally, the HCP exhibited great hypoglycemic activity in vitro and the concentration-dependent. When the concentration was 1 mg/mL, the inhibition ability of α-glucosidase and α-amylase reached 83.02% and 78.65% respectively. This experiment indicated that HCP had the potential to become functional raw materials for hypoglycemic preparations.